Critical Community Psychology and Qualitative Research: A Conversation. (February 2014) - Nelson, Geoffrey; Evans, Scot D.
This article is a conversation between two critical community psychologists about the compatibility and theoretical connections between their field and qualitative research. Critical community psychology is driven by values of power-sharing and social justice, and is praxis-oriented, emphasizing solidarity with oppressed people to create transformative social change. The authors argue that qualitative research, by itself or mixed with quantitative methods, can enhance both epistemic and transformative psychopolitical validity in critical community psychology. Implications of this theoretical/methodological approach for action and social change are discussed.